GAME ONLINE DAN AGRESIVITAS ANAK USIA SMP DI SIDOARJO - Vetty Putri Tanjung (Universitas Muhammadiyah Sidoarjo, 2015)
The purpose of this study was to analyze the effects of online games towards aggressiveness of junior high school students in Sidoarjo Regency. This research used a quantitative research through an explanatory approach. The sampling technique in this study was a random sampling of 100 students in the Krian District, Sidoarjo Regency. Analyzing data used linear regression. The results showed that the online games that is currently booming in Sidoarjo Regency were Game Action Adventure (78.2%), Game action